Faktor-Faktor yang Mempengaruhi Kurangnya Kesadaran Mahasiswi AKBID Saleha Terhadap Penggunaan Masker di Masa Pandemi COVID-19 di AKBID Saleha Banda Aceh Tahun 2021 - Desria Mauliati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The use of masks is one of the health protocols that must be followed by everyone with discipline. The results of monitoring Compliance with Health Protocols for wearing masks on female students at the Saleha Midwifery Academy Banda Aceh in 2021 are around 75% of all grades 1,2 and 3 students. Research Objectives: to determine the effect of knowledge, environment and behavior on female students at AkbidSaleha Banda Aceh. Research Methods: This study used an analytical method with a Cross Sectional approach which was carried out on 26-27 August 2021. The population in this study were all AkbidSaleha students who totaled 92 people. Sampling using total sampling.Analysis of data using univariate and bivariate analysis with the chi-square method. Results: The results of statistical tests with Chi-Square obtained p Value = 0.000 <0.05, there is an effect of knowledge of student AkbidSaleha with a lack of awareness of the use of masks. While the results of statistical tests with Chi-Square obtained p Value = 0.000 <0.05, there is an environmental influence with a lack of awareness of the use of masks in AkbidSaleha students. And the results of statistical tests with Chi Square obtained p value = 0.000 <0.05, there is an influence of behavior with a lack of awareness of the use of masks in AkbidSaleha students